La crise du secteur phoenicicole dans les pays méditerranéens. Quelles recherches pour y répondre? - Ferry M. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
Because of the stretch of the desert hot areas in the South Mediterranean countries and on account of the adaptation of the date palm to oasis agroecological conditions and of its economic and cultural interest, date palm farming has a great importance in all the countries of North Africa and Near East. About one third of the world total number of date palms is cultivated in the Mediterranean area. But, Mediterranean date palm farming is in crisis: irrigation water is more and more scarce and/or expensive; the degradation of soils, ground water and steppe rangelands is increasing; traditional oasis are less and less productive and modern plantations are often based on farming systems that are fragile and present a high economic and ecological risk. Important investments have been made by governments. They have contributed to an increase of date production but this production has always remained very inferior to the population increase. There exist examples of successful development or efficient crisis resistance: Israel date palm farming, farming systems at the cities periphery that compensate the insufficient farm surface by multiactivity, well sized farms that dispose of adequate manpower, water resources and market. In the South and North Mediterranean countries, scientific teams are carrying out various research studies on date palm. Are these research studies adapted to the priority problems set by the Mediterranean date palm farming crisis?.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)